F150 Non-invasive brain stimulation is safe in children: Evidence from 3 million stimulations. (May 2018) - Zewdie, Ephrem; Ciechanski, Patick; Kuo, Hsing-Ching; Giuffre, Adrianna; Cole, Lauran; Seeger, Trevor; Damji, Omar; Jamie, Keess; Hodge, Jacquie; Jadavji, Zeanna; Kahl, Cynthia; McLellan, Quinn; et al.
Abstract : Introduction: Non-invasive brain stimulation can interrogate neurophysiology and therapeutically modulate brain function. Transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) are the primary modalities. Despite such potential, experience in the developing brain has been limited. We conducted a large, prospective study of children undergoing brain stimulation to determine safety and tolerability across diverse modalities and populations. Methods: Our academic pediatric center established a non-invasive brain stimulation laboratory for children in 2008. Multi-disciplinary neurophysiological studies included single- and paired-pulse TMS methods. Therapeutic clinical trials used repetitive TMS (rTMS) and anodal/cathodal standard and high definition (HD) tDCS. Motor mapping used robotic TMS (Axilium). Prospective, standardized safety and tolerability data was obtained on all subjects including a pediatric TMS measure and child and parental interviews. Results: From 2008 to 2017, 390 children underwent brain stimulation (median 13.2 years, range 0.7–18). Most common were perinatal stroke/cerebral palsy (80), typically developing (80), and mild traumatic brain injury (73). There were no serious adverse events. Tolerability between single and paired-pulse TMS (459, 240 stimulations) and rTMS (2.6 million stimulations) was comparable and rated similar to a long car ride. Even though >100 participants had brain injuries and/or epilepsy, no seizures occurred. Headache following a long TMS neurophysiology protocol was more common in perinatal stroke (40%) than typically developing (13%) participants but was mild and self-limiting. Mild neck pain was reported but comparable between perinatal stroke (22%), depression (19%), and TBI (19%). Tolerability improved over time with rates of all symptoms decreasing by >50% on repeat testing. One of 40 adolescents with depression withdrew from a high-frequency rTMS trial due to discomfort. Following robotic TMS motor mapping, headache was reported by 11%, 20% and 50% of typically developing, perinatal stroke and Tourette syndrome participants. Neck pain appeared to be more common with robotic TMS compared to manual TMS in typically developing children (33% vs 3%). Mean tolerability scores for robotic TMS (4.3 ± 1.5) were comparable to manual TMS (4.2 ± 1.3). Of 65 children receiving tDCS and 9 receiving HD-tDCS, scalp itching in 55% was mild, transient, and comparable to sham. Sensation and tolerability between tDCS and HD-tDCS was comparable. There were no reports of disease-specific outcomes worsening with stimulation. For example, neither low frequency rTMS ( n = 45) nor cathodal tDCS ( n = 33) of the non-lesioned motor cortex decreased function of either hand in children with hemiparetic cerebral palsy. Conclusion: Non-invasive brain stimulation is safe and well tolerated in children and should be considered minimal risk. Applications in the developing brain should be advanced.